(untitled) (Research, Society and Development, 2021)
Sanchezia oblonga Ruiz & Pav. is an ornamental and floristic species, widely used in landscaping and domestic gardens, acting as one of the main food sources for the maintenance of pollinators during the winter season. The objective of this work was to evaluate the influence of leaves and the size of cuttings on the rooting of sanchesia. This work consisted of two experiments, both of which were conducted in a shade house at the Forest Nursery of the Federal Technological University of Paraná - Câmpus Dois Vizinhos (UTFPR-DV). The experimental design was completely randomized (DIC), with three treatments, four replications of 10 cuttings per plot. The first experiment consisted of making cuttings that were standardized at 6 cm in length, and the treatments consisted of cuttings without leaves, with a pair of leaves cut in half and cuttings with two pairs of leaves cut in half. In the second, cuttings with three different lengths (6, 12 and 18 cm) were evaluated and with a pair of leaves cut in half. In both experiments, the cuttings were planted in 120 cm³ tubes containing the vermiculite substrate in fine granulometry. After 73 days, rooting percentages, survival, mortality, shoots, number and average length of roots per cut and number of shoots were analyzed. Regarding the size of the cuttings, there was no significant difference, however, it was found that the species is easily propagated by the cutting technique, since the general rooting average was 98.86%. The rooting of cuttings with leaves was superior when compared to cuttings without leaves, therefore, it is recommended to use cuttings with one or two pairs of leaves reduced to half leaf for the production of seedlings of this species.